Technological tools as a trend in secondary education in times of COVID-19: Theoretical review - Núñez-Naranjo, Aracelly (2022)
The pandemic caused by Covid-19, led to a change in the educational field, which involved working from home with technology to give continuity to classes and interaction between educational subjects. Technological advances strengthened education. This article analyzes the trend of technological tools in the teaching process of high school students. Methods of content analysis and systemic and analytical review of the literature were used. As a result, he obtained that the most used and constantly changing educational technologies are social networks, platforms, multimedia resources, virtual reality, augmented reality, artificial intelligence, big data, among others. It is concluded that networks, collaborative platforms and multimedia resources are being developed on a larger scale for educational purposes in the pandemic, and that social technologies are currently in constant innovation associated with education.